Principles of direct and database marketing : a digital orientation. - Tapp, Alan, ....- (Harlow : Prentice Hall, 2008)
This market-leading, forward thinking textbook comprehensively addresses the impact of new technologies on the principles and practices of Direct Marketing. New features include: · A new chapter on Web 2.0, reflecting on the internet's failures and successes, and digital developments looking forward. · Cutting edge, international case study material from Sport England, Volvo, Tesco.com, Tower Hamlets and the charity Personal Action, linking theory to practice. · Major expanded themes in the book include buyer behaviour and empowerment; budgeting; and CRM. · Full, critical discussion of hot topics such as privacy, credit and fraud issues that gets behind the jargon.